iProcure or shariah compliant procurement framework for wakaf and zakat funded buildings and infrastructure works - Abdul Rashid, Khairuddin; Mohd Fauzi, Puteri Nur Farah Naadia (Universiti Sains Islam Malaysia (USIM), 2017)
The paper reports on a study to develop a proposed Shariah compliant construction procurement framework or hereinafter referred to as iProcure. The idea for the study was prompted when it was realized that there is a dichotomy in the way in which construction related business transactions are being conducted. On the one hand tools for and the use of Shariah compliant business transactions are on the rise but on the other hand business transactions concerning the procurement of buildings and infrastructure works, including those funded by Shariah compliant funding mechanisms and wakaf and zakat, still use the conventional/western styled contract arrangement. There is a concern that the latter may not be meeting the requirements of Shariah. Therefore parties involved therein could be conducting business transactions that may be considered syubhah. Methodology used for the study involved reviewing literature on Islamic principles on business transaction or al-muamalat and imbedding them into the conventional and western styled contract arrangement. The symbiosis of these two practices give birth to a theoretical Shariah compliant procurement framework for building and infrastructure works. Thereafter, a series of focused discussion with academics specializing in the Shariah and construction procurement was conducted to firm-up the framework. The outcome of the study is a proposed Shariah compliant construction procurement framework or iProcure. The study’s findings is significant in two ways: firstly it highlights the importance of the concept of Shariah compliant construction procurement and therefore improves the prospect of its application in future transactions. Secondly the application of Shariah compliance principles into the practice of construction procurement would facilitate minimizing or alleviating the presence of syubhah in future construction related business transactions. iProcure is targeted towards key players of the construction sector and policy makers in their future construction related business transactions or policies’ formulation respectively especially those works related to or funded by wakaf and zakat.